2006
DOI: 10.1111/j.1365-2125.2006.02770.x
|View full text |Cite
|
Sign up to set email alerts
|

Duloxetine pharmacokinetics are similar in Japanese and Caucasian subjects

Abstract: What is already known about this subject• The pharmacokinetics of duloxetine have been assessed in a number of clinical studies.• Duloxetine is eliminated through oxidative metabolism via CYP1A2 and, to a lesser degree, CYP2D6.• There is strong evidence that the prevalence of CYP2D6 phenotypes and the activity of CYP1A2 enzyme activity differ between Japanese and Caucasians.• Given the characteristics of duloxetine metabolism, there is good reason to assess pharmacokinetic differences between Japanese and Cauc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 6 publications
(14 reference statements)
3
26
1
Order By: Relevance
“…For example, in three studies, the combined average maximal plasma concentration (C max ) following single dose administration of 20 mg, 40 mg, or 60 mg of duloxetine was 22.9 ng/mL (n = 16), 46 ng/mL (n = 24), and 69.6 ng/mL (n = 12), respectively 20,21,29 ; whereas average C max values from two other studies for single dosage 20, 40, and 60 mg duloxetine yielded 13.7 ng/mL (n = 22), 27.8 ng/mL (n = 16), and 42.2 ng/mL (n = 16), respectively. 19,22 The levels obtained in the latter two studies were consistently found to be 0.6 times those of the former three studies across all single dosage regimens, although the basis for this difference is uncertain. According to the manufacturer, duloxetine has an elimination half-life (t 1/2 ) of about 12 h (range 8-17 h).…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…For example, in three studies, the combined average maximal plasma concentration (C max ) following single dose administration of 20 mg, 40 mg, or 60 mg of duloxetine was 22.9 ng/mL (n = 16), 46 ng/mL (n = 24), and 69.6 ng/mL (n = 12), respectively 20,21,29 ; whereas average C max values from two other studies for single dosage 20, 40, and 60 mg duloxetine yielded 13.7 ng/mL (n = 22), 27.8 ng/mL (n = 16), and 42.2 ng/mL (n = 16), respectively. 19,22 The levels obtained in the latter two studies were consistently found to be 0.6 times those of the former three studies across all single dosage regimens, although the basis for this difference is uncertain. According to the manufacturer, duloxetine has an elimination half-life (t 1/2 ) of about 12 h (range 8-17 h).…”
Section: Discussionmentioning
confidence: 67%
“…80 kg 27 ). Compilation of data from other studies generates an average V d of 1563 l (%19.5 L/kg) for 118 subjects, [19][20][21][22]28 with a reported average ranging from 962 l (%12 L/kg) for the 12 non-elderly subjects in the study by Skinner et al, 20 up to 2909 l (%36.4 L/kg) for the 6 healthy subjects examined by Suri and colleagues. 19 Although blood levels increase in approximate proportionality to dosage 29 (up to 60 mg/day, see below), the pharmacologic investigations show an apparent dichotomy in the peak levels obtained.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…These results appear to hold in studies comparing different ethnic samples (8,9). As duloxetine has a dual effect on both the serotonin and norepinephrine systems (10), it appears to be a viable therapeutic option for treating depressive disorders, effective in the management of somatic symptoms, especially pain, more frequently present depressed non-Westernized populations (11).…”
Section: To the Editorsmentioning
confidence: 96%